Application of Job Safety Analysis with Work Accidents in the Refinery Section - Sri Muliani Ayii; Muh Multazam; Nasruddin Syam (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
JSA is a comprehensive approach to identifying, analyzing, and formulating corrective measures to reduce dangerous risks while working. This study aims to determine the application of job safety analysis to work accidents in the refinery section of Pt. Aneka Tambang UBPN Kolaka in 2023. The type of research used is quantitative research with a cross-sectional approach. The population in this study is all workers in the refinery section of PT. ANTAM UBPN Kolaka has 78 workers. Data were taken using questionnaires and analyzed with univariate and bivariate tests with confidence levels α=0.05. The results of this study showed that the variables that have a significant relationship with work accidents in workers are hazard identification, with a p-value of 0.005; risk assessment, with a p-value of 0.035; and risk control, with a p-value of 0.023. It can be concluded that there is a relationship between hazard identification and risk assessment with work accidents in the refinery section. It is recommended that refinery supervisors provide education about hazards and risks, which is very important to prevent occupational accidents and carry out occupational safety and health properly and correctly